Analysis of The Effect of Financial Ratios on ROA In Islamic Commercial Banks in Indonesia - Murtiningrum, Widiastuti (International Journal of Islamic Business and Management Review, 2023)
Currently, Islamic banks are growing rapidly, starting in 1983, where BI gave freedom to banks to set interest rates, in order to create a healthy and strong bank, by implementing a profit-sharing system. The potential for the development of Islamic banks is very open, to become a leading bank at the global level. One of the government's missions is to develop the halal industry, making Islamic banks large and powerful in the country with the largest Muslim population in the world. For this reason, research was conducted by analyzing the ratio of finance to profitability at Islamic Banks from 2010 to 2022. The population in the study was 8 out of 14 Islamic banks, which are registered with OJK and have complete financial statements published with purposive sampling. Data analysis method with panel data regression using SPSS 25 and eviews 10. From the results of the t test, it is hypothesized that CAR and FDR have no influence on ROA, while NPF and BOPO have a negative influence on ROA. The variables CAR, FDR, NPF and BOPO simultaneously have a significant influence on the ROA of Islamic Banks for the period 2010 – 2022. The coefficient of determination is 53.5% and the remaining 46.5% comes from factors other than variables in the study.